Rechtsvacuum Phenomenon Military Administrative Court Arrangements - Gustirada, Anggun; Sunardi, Sunardi; Muhibbin, Moh (Widya Yuridika, 2024)
This article aims to deconstruct a comprehensive analysis to answer the problem of rechtvacuum in the military administrative justice system. Historically, military administrative court judges have rejected challenges to military administrative decisions on the grounds that there are no implementing regulations from the military justice law. Even the state administrative court also rejected the lawsuit of the military administrative decision because it was not his competence. The research method used is normative juridical with a statutory and conceptual approach, with descriptive analytical techniques. Based on the results of the analysis, it can be said that the consequences of the rechtvacuum of the military administrative court create legal uncertainty and human rights are ignored and as if members of the army are immune to the law. Then a judge is not allowed to reject a case on the basis that there is no punishment.